Zatoichi and the Chest of Gold Based on a Short Story by Kan Shimozawa - Ikehiro, Kazuo; Miyagawa, Kazuo; Katsu, Shintaro; Shimada, Shôgo; Tsubouchi, Mikiko (Zatoichi: The Blind Swordsman Collection, 2019)
After arriving in a small village, Zatoichi finds himself accused of stealing the citizens' hefty tax payments. To clear his name, he must face off against a corrupt official, a succession of hired blades, and a bullwhip-wielding titan, played by star Shintaro Katsu's brother Tomisaburo Wakayama. This sixth installment of the increasingly popular and prestigious Zatoichi series features ravishing visuals by Rashomon cinematographer Kazuo Miyagawa. [www.criterion.com]